A new virus A/H1N1, a new pandemic: a continuing risk to a globalized humanity - Osores Plenge, Fernando (2009)
Influenza is a highly contagious disease. There are some historical descriptions of this condition by ancient Greek physicians, and the etiological agents have been known only for the last eight decades. The causative agent is the influenza virus, which has three main types: A, B, and C. Type A is capable of circulating within many different biological reservoirs, including humans, swine, and birds. It also has high genetic variability, which allows it to have minor antigenic drifts or mutations which are responsible of epidemics in humans. Sometimes changes are quite marked, leading to pandemics.In a globalized world, with more than 6 billion inhabitants, with many social inequities and evident climate changes, influenza viruses are a permanent risk for mankind.Clinical features for the different viral subtypes may vary from subtle infections to full blown and severe, life-threatening forms. Event with the great advances in diagnostics and immunization, the manufacture and distribution of new diagnostic kits may take some time, and new vaccines are not always readily available. Specific therapies against influenza are not well developed. There are two groups of drugs, the so called adamantane derivatives, such as amantadine and rimantadine, and the neuraminidase inhibitors, such as oseltamivir and zanamivir. Most vulnerable areas for the new flu pandemics include developing countries, particularly the poorest ones, so that the greatest effort must be made for helping these areas.